Efficient Vanadium‐Catalyzed Aerobic C−C Bond Oxidative Cleavage of Vicinal Diols. Issue 17 (24th May 2018) - Amadio, Emanuele; González‐Fabra, Joan; Carraro, Davide; Denis, William; Gjoka, Blerina; Zonta, Cristiano; Bartik, Kristin; Cavani, Fabrizio; Solmi, Stefania; Bo, Carles; Licini, Giulia
Abstract: The aerobic oxidative C−C bond cleavage of vicinal diols catalyzed by vanadium amino triphenolates is described. Our results show that C−C bond cleavage can be performed in different solvents, under an air or oxygen atmosphere, with a large variety of glycols (cyclic or linear, with aromatic or aliphatic substituents) affording the corresponding carbonyl derivatives with high chemoselectivity. Reactions can be performed with as little as 10 ppm of catalyst reaching TON up to 81, 000 and TOFs of up to 4150 h −1 . A reaction mechanism, rationalized by density functional theory calculations, is also proposed. Abstract :